2021
DOI: 10.3390/molecules26154411
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Lemon (Citrus limon) Extract Overcome TNF-α-Induced Insulin Resistance in Cultured Adipocytes

Abstract: The consumption of plant-based food is important for health promotion, especially regarding the prevention and management of chronic diseases such as diabetes. We investigated the effects of a lemon extract (LE), containing ≥20.0% total flavanones and ≥1.0% total hydroxycinnamic acids, on insulin signaling in murine 3T3-L1 adipocytes treated with TNF-α, which was used to mimic in vitro the insulin resistance condition that characterizes diabetes mellitus. Our results showed LE increased PPARγ, GLUT4 and DGAT-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Polyphenols have antioxidant and anti-infammatory properties, and favonoids in particular have been shown to have the ability to improve insulin sensitivity and regulate lipid metabolism [46]. Studies have shown that increasing fruit intake can reduce the risk of cardiovascular disease mortality, hypertension, and stroke [44], and fermented apple juice can efectively inhibit weight gain and regulate blood lipid levels [43].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols have antioxidant and anti-infammatory properties, and favonoids in particular have been shown to have the ability to improve insulin sensitivity and regulate lipid metabolism [46]. Studies have shown that increasing fruit intake can reduce the risk of cardiovascular disease mortality, hypertension, and stroke [44], and fermented apple juice can efectively inhibit weight gain and regulate blood lipid levels [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have explored the development of insulin resistance using adipocyte culture cell lines, such as 3T3-L1 adipocytes. It has been reported that insulin resistance inducers, including tumor necrosis factor (TNF)-α, reduced the activities and/or expressions of lipoprotein lipase ( Lpl ), an enzyme associated with triglyceride uptake in adipocytes [ 1 , 2 ]; glycerol-3-phosphate dehydrogenase 1 ( Gpd1 ) and diacylglycerol transferase 1 ( Dgat1 ), enzymes involved in triglyceride synthesis [ 3 , 4 ]; Cidec , an enzyme involved in lipid droplet production [ 5 ]; and adiponectin ( Adipoq ), an insulin sensitivity hormone [ 6 ]. A recent study demonstrated that insulin resistance induced by TNF-α in 3T3-L1 adipocytes was restored by rosiglitazone, an agonist of the peroxisome proliferator-activated receptor (PPAR) γ2 (PPARG2), an important nuclear receptor for adipocyte differentiation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Signaling pathways, bioactive compounds, and miRNAs are all recognized to have a role in the creation and progression of illness. [26][27][28] Extracellular vesicles are important intercellular communication factors that carry a variety of bioactive substances (e.g., inflammatory factors, adipokines, and some kinases), [29][30][31] as well as being involved in the transmission of disease-related signaling pathways (PI3K/Akt pathway, an important insulin signaling pathway). [32][33][34] In addition, IR has been linked to dynamic changes in exosome composition as well as aberrant miRNA expression in extracellular vesicles (early exercise intervention).…”
mentioning
confidence: 99%